The postpartum nutrition cookbook : 100+ nourishing recipes for new moms - Licalzi, Diana; Reaver, Ashley (Blue Star Press, 2024)
"The essential postpartum recovery guide and cookbook to help new moms replenish their bodies with 100+ easy, nutrient-packed recipes, plus meal plans and shopping lists. The postpartum period brings major physical and emotional changes for new moms. While caring for a newborn is difficult, it's critical that mothers focus on replenishing their bodies after pregnancy, childbirth, and breastfeeding. Most postpartum resources focus on how to care for the baby, but The Postpartum Nutrition Cookbook--written by registered dietitians Diana Licalzi and Ashley Reaver--prioritizes the mom's self-care first. This book guides new moms through recovery during the 4th trimester, highlighting key nutrients needed to heal and restore their bodies."--